2006
DOI: 10.1177/153537020623101007
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Exposure to Diesel Exhaust Particles Enhances Coagulatory Disturbance with Endothelial Damage and Systemic Inflammation Related to Lung Inflammation

Abstract: Pulmonary exposure to diesel exhaust particles (DEP) enhances lung inflammation related to bacterial endotoxin (lipopolysaccharide [LPS]) in mice. Severe lung inflammation can reportedly induce coagulatory abnormalities and systemic inflammation. This study examined the effects of components of DEP on lung inflammation, pulmonary permeability, coagulatory changes, systemic inflammatory response, and lung-to-systemic translocation of LPS in a murine model of lung inflammation. ICR mice were divided into six exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 28 publications
7
59
0
Order By: Relevance
“…In addition, one intriguing aspect of the epidemiologic data is that health effects of PM 2.5 are primarily seen in subjects with predisposing factors, including pneumonia, asthma, chronic obstructive pulmonary disease, compromised immune systems, and age over 65 years old [3]. Consistent with the epidemiological studies, we have experimentally demonstrated that diesel exhaust particles (DEP), major contributors to environmental PM 2.5 in urban areas, exhibit respiratory toxicity with or without predisposing factors in vivo [4][5][6][7][8][9][10].…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…In addition, one intriguing aspect of the epidemiologic data is that health effects of PM 2.5 are primarily seen in subjects with predisposing factors, including pneumonia, asthma, chronic obstructive pulmonary disease, compromised immune systems, and age over 65 years old [3]. Consistent with the epidemiological studies, we have experimentally demonstrated that diesel exhaust particles (DEP), major contributors to environmental PM 2.5 in urban areas, exhibit respiratory toxicity with or without predisposing factors in vivo [4][5][6][7][8][9][10].…”
Section: Introductionsupporting
confidence: 61%
“…In addition, LPS is a significant constituent of many air pollutant particles and has accordingly been implicated in the adverse effects of PM [33]. In accordance with the close links among LPS, lung inflammation (injury), and PM, we have previously shown that intratracheal administration of DEP and their components facilitates lung inflammation induced by LPS [8,34] and subsequent systemic inflammation with coagulatory disturbance [9].…”
Section: Effects Of Nanoparticles On Acute Lung Inflammation Induced mentioning
confidence: 69%
“…In our study, we observed that a single pulmonary exposure to DEP (8 mg·kg À1 ) significantly increased the serum level of fibrinogen (4.261 ± 0.248 g·L À1 ; unpublished data), which is involved in fibrin (clot) formation, as compared to that of vehicle (3.356 ± 0.110 g·L À1 ). Interestingly, the carbonaceous nuclei of DEP obtained after extraction with dichloromethane (CH 2 Cl 2 : referred to as 'washed DEP' 4 mg·kg À1 ) further increased the level of fibrinogen (4.883 ± 0.371 g·L À1 ) in the same experiment (Inoue et al, 2006), suggesting that the organic chemical component in DEP extracted with CH 2 Cl 2 (referred to as 'DEP-OC') includes elements that have the potential to suppress the synthesis of fibrinogen. Therefore, it should be noted that the role each individual DEP component plays in the regulation of the coagulation system and resultant vascular thrombotic events induced by DEP is complicated.…”
mentioning
confidence: 89%
“…Thus it has been shown that IL-6 triggers production of metalloproteinase inhibitors, such as alpha 2-macroglobulin by perivascular astrocytes [17], resulting in BBB failure and perivascular cerebral edema. Also elevated circulating levels of IL-6 have been reported to enhance pulmonary permeability and endothelial damage in different conditions, such as ischemia-perfusion during lung transplantation [18], pulmonary exposure to diesel [19], or intestinal ischemia [20]. Moreover other proinflammatory cytokines, such as TNF-α, IL-1β and IFN-γ (Interferon-γ) have been shown to increase pulmonary permeability, resulting in pulmonary edema [21].…”
Section: Methodsmentioning
confidence: 99%